2020
DOI: 10.1039/d0an01268h
|View full text |Cite
|
Sign up to set email alerts
|

Chemically robust succinimide-group-assisted irreversible bonding of poly(dimethylsiloxane)–thermoplastic microfluidic devices at room temperature

Abstract: This study investigates surface chemical modification using anhydride silane and amino silane reagents at room temperature (RT) to realize bonding between silicon-based PDMS and non-silicon thermoplastics. The anhydride silane has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Borysiak et al reported maximum pressures of 4.1 bar without failure for bonding of SEBS to itself, PS, or glass surfaces applying 75 • C for 30 min [26]. When compared to PDMS bonded to itself [41], glass [42], or thermoplastics [43][44][45], similar or even higher values of bonding strength can be achieved using our presented TPE-based approach (Table 1), even after 7 days of exposure to buffer. Preventing the absorption of molecules from the solution into the bulk materials of the chips is of upmost importance due to the high surface-to-volume ratios seen in microfluidic systems, which can lead to the rapid drop of concentrations in the perfused solution [46].…”
Section: Device Bonding Strategiesmentioning
confidence: 53%
See 1 more Smart Citation
“…Borysiak et al reported maximum pressures of 4.1 bar without failure for bonding of SEBS to itself, PS, or glass surfaces applying 75 • C for 30 min [26]. When compared to PDMS bonded to itself [41], glass [42], or thermoplastics [43][44][45], similar or even higher values of bonding strength can be achieved using our presented TPE-based approach (Table 1), even after 7 days of exposure to buffer. Preventing the absorption of molecules from the solution into the bulk materials of the chips is of upmost importance due to the high surface-to-volume ratios seen in microfluidic systems, which can lead to the rapid drop of concentrations in the perfused solution [46].…”
Section: Device Bonding Strategiesmentioning
confidence: 53%
“…Borysiak et al reported maximum pressures of 4.1 bar without failure for bonding of SEBS to itself, PS, or glass surfaces applying 75 °C for 30 min [ 26 ]. When compared to PDMS bonded to itself [ 41 ], glass [ 42 ], or thermoplastics [ 43 , 44 , 45 ], similar or even higher values of bonding strength can be achieved using our presented TPE-based approach ( Table 1 ), even after 7 days of exposure to buffer.…”
Section: Resultsmentioning
confidence: 92%
“…After bonding the PDMS with the substrates, the assembly is pulled apart. Although this pull test is performed in several works (e.g., by the team of Nae Yoon Lee [43][44][45][46][47]), it might have some drawbacks. Although cohesive failures can be easily distinguished from adhesive failures, the tensile strength cannot be adequately calculated in the latter case.…”
Section: Tensile Strength Measurementsmentioning
confidence: 99%
“…For the sake of better comparability between different structures/geometries, besides the absolute maximum flow rates (expressed in mL/min), the ratio of the liquid volume that flows through the channel within 1 min and the channel volume is also frequently given (expressed as flow-volume/channelvolume/min). Without a doubt, this is one of the most widespread methods for testing microchannel functionality [19,35,36,38,[43][44][45][46][47]56,57].…”
Section: Leakage Testmentioning
confidence: 99%
See 1 more Smart Citation